Parameter Genetik Hasil Persilangan Jagung Bersari Bebas untuk Mendapatkan Galur Berbiji Ungu - Hanif Kusuma Abadi; Eries Dyah Mustikarini; Gigih Ibnu Prayoga (Jurnal Ilmu Pertanian Indonesia, 2021)
Corn (Zea mays) is a cereal crop and has become a staple food. Purple corn has more excess compared to corn in general. In addition, purple corn has high nutrient content and anthocyanin levels. This study aims to determine genetic parameters such as variability, heritability, and genetic advance of the F2 generation resulting from an open-pollinated hybridization. The research was conducted from January 2020 to June 2020 on the Research and Experimental Field of the Department of Agrotechnology, Universitas Bangka Belitung. The work used a single plant design. The lines used were derived from the results of the previous selection stage. The results showed that the phenotype variability was relatively wide on the weight character of ear cobs with cornhusk, and the cob weight without cornhusk. High heritability values are found in the characters of harvest age, age of male flowering, and age of female flowering. The value of expected genetic advance for high expectations is found in the characters of plant height, the row number of seeds, the weight of 100-seeds, and the weight of cob with cornhusk. The selection results suggest nine corn lines that can be used for the next generation selection. Keywords: corn, expected genetic advance, heritability, purple, variability